Empowering the Community of Plaosan Village Through Tempe Katsu Processing as an Innovation in Fast Food Based Entrepreneurship - Hasbullah, Afif; Wangi, Nisaul Barokati Seliro; Rajif , Salim Ahmad (STAI Miftahul ULa Nganjuk, 2024)
Plaosan Village has significant potential in tempe production; however, its utilization remains suboptimal. The majority of tempe produced in this village is sold in its raw form, lacking further processing that could enhance its economic value. In order to empower the community, a training program on the production of tempe katsu, an innovative tempe-based product, was conducted. This product has the potential to serve as a fast food item with a higher market value. The approach used in this community engagement program was Asset-Based Community Development (ABCD), which encourages active involvement from the community in the process of change. The objective of this program was to increase creativity, develop entrepreneurial skills, and enhance the income of the community through the production of tempe katsu, which can be marketed locally. The results of the training showed an improvement in the community's understanding of how to process tempe into a value-added product, with the potential for developing small and medium-sized enterprises (SMEs) based on tempe in the village.